2022
DOI: 10.3389/fnut.2022.1037696
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the pleiotropic effects of butyrate as a potential therapeutic agent on NAFLD management: A systematic review

Abstract: Non-alcoholic fatty liver disease (NAFLD) is one of the most common chronic diseases worldwide. As a multifaceted disease, NAFLD’s pathogenesis is not entirely understood, but recent evidence reveals that gut microbiota plays a significant role in its progression. Butyrate, a gut microbiota metabolite, has been reported to have hepato-protective effects in NAFLD animal models. The purpose of this systematic review is to determine how butyrate affects the risk factors for NAFLD. Searches were conducted using re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 117 publications
0
14
0
Order By: Relevance
“…The PC supplementation partially restored the HFHF-induced decrease in SCFAs, such as butyrate and acetate contents. Butyrate can especially significantly relieve steatohepatitis by regulating the gut microbiota and intestinal barrier function, thereby reducing inflammation and oxidative damage in the liver, and it also has a good effect on blood glucose and energy balance [64].…”
Section: Discussionmentioning
confidence: 99%
“…The PC supplementation partially restored the HFHF-induced decrease in SCFAs, such as butyrate and acetate contents. Butyrate can especially significantly relieve steatohepatitis by regulating the gut microbiota and intestinal barrier function, thereby reducing inflammation and oxidative damage in the liver, and it also has a good effect on blood glucose and energy balance [64].…”
Section: Discussionmentioning
confidence: 99%
“…The study findings indicate that the administration of NaB resulted in a clinically significant decrease in serum concentrations of ALT and AST although it did not reach a statistically significant level. The impact of butyrate on hepatic enzymes exhibits variability throughout animal-based investigations [54]. While numerous studies have demonstrated the hepatoprotective properties of butyrate, its efficacy has been inconsistent in some investigations [54].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it helps maintain the integrity of the intestinal barrier, reducing endotoxin entry into the bloodstream and thereby enhancing the body’s antioxidative defenses via the gut-liver axis [ 66 ]. Secondly, butyrate activates the Nrf2 pathway, promoting the expression of antioxidative enzymes and alleviating oxidative stress in liver cells [ 67 ]. Additionally, butyrate effectively inhibits oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 99%